Design and synthesis of a new topical agent for halting blood loss rapidly: a multimodal chitosan-gelatin xerogel composite loaded with silica nanoparticles and calcium - Patil, Gokul; Torris, Arun; Suresha, P. R.; Jadhav, Sachin; Badiger, V. Manohar; Ghormade, Vandana (Colloids and Surfaces B-Biointerfaces, 2021)
Uncontrolled hemorrhage often causes death during traumatic injuries and halting exsanguination topically is a challenge. Here, an efficient multimodal topical hemostat was developed by (i) ionically crosslinking chitosan and gelatin with sodium tripolyphosphate for (ii) fabricating a robust, highly porous xerogel by lyophilization having 86.7 % porosity, by micro-CT and large pores similar to 30 mu m by SEM (iii) incorporating 0.5 mg synthesized silica nanoparticles (SiNPs, 120 nm size, -22 mV charge) and 2.5 mM calcium in xemgel composite that was confirmed by FTIR analysis with peaks at 3372, 986 and 788 cm(-1), respectively. XPS analysis displayed the presence of SiNPs (Si2p peak for silicon) and calcium (Ca2p1, Ca2p3 transition peaks) in the composite. Interestingly, in silico percolation simulation for composite revealed interlinked 800 mu m long-conduits predicting excellent absorption capacity and validated experimentally (640 % of composite dry weight). The composite achieved >16-fold improved blood clotting in vitro than commercial Celox and Gauze through multimodal interaction of its components with RBCs and platelets. The composite displayed good platelet activation and thrombin generation activities. It displayed high compressive strength (2.45 MPa) and withstood pressure during application. Moreover, xerogel composite showed high biocompatibility. In vivo application of xerogel composite to lethal femoral artery injury in rats achieved hemostasis (2.5 min) significantly faster than commercial Celox (3.3 min) and Gauze (4.6 min) and was easily removed from the wound. The gamma irradiated composite was stable till 1.5 yr. Therefore, the xerogel composite has potential for application as a rapid topical hemostatic agent.
Keywords: Hemostatic; Polymer; silica nanoparticles; Xerogel

Synthesis of N-oxyethylene substituted imidazolium-based zwitterions as a recyclable solvent for cellulose dissolution - Jadhav, Sachin; Ganvir, Vivek; Singh, Madan Kumar; Shanmuganathan, Kadhiravan (Cellulose, 2023)
Cellulose is a readily available, renewable, and natural biomaterial that has the potential to replace synthetic fibres. However, their processing to shaped materials such as fibre or film is still complex and restricted due to its insolubility in most conventional solvents. Herein, we present the synthesis and cellulose dissolution characteristics of a new class of recyclable zwitterions composed of tethered N-oxyethylene substituted imidazolium cation and alkyl carboxylate anion. Investigations on cellulose dissolution showed that increasing the alkyl chain length of carboxylate anion and introduction of oxyethylene unit on imidazolium ring led to better cellulose dissolution ability, and up to 12% (w/w) cellulose could be dissolved in aqueous zwitterions at 105 degrees C. The thermal behavior of zwitterions and their cellulose solutions was characterized by TGA and found to be more stable than the NMMO and Lyocell solutions. Rheological characterization of cellulose solutions revealed viscoelastic behavior and zero shear viscosity of 6-12% (w/w) cellulose solution in hexanoate containing aqueous zwitterion was 555 to 5900 Pa.s at 120 degrees C. The characteristics of cellulose solution indicate its potential for processing to cellulose fibre by extrusion through a tiny spinneret. Physico-chemical analysis of regenerated cellulose indicates that zwitterions cause no adverse effect on cellulose structure and morphology during dissolution. The zwitterions are recovered after the cellulose regeneration process, and the recovery was found to be 99.6% after purification using the ion-exchange method.
Keywords: Carboxylate anion; Cellulose dissolution; Oxyethylene unit; Regenerated cellulose; Rheology; zwitterions

Structure and properties of the cellulose fibres spun from imidazolium-based carboxylate functionalized zwitterionic liquid - Jadhav, Sachin; Singh, Dhirendra; Gupta, Deepika; Ganvir, Vivek; Singh, Madan Kumar; Shanmuganathan, Kadhiravan (CARBOHYDRATE POLYMERS, 2025)
Keywords: cellulose; Direct dissolution; Zwitterionic liquid